The Role of Parents in Early Childhood's Emotional Social Development - Nopia Yuliandari; Dadan Suryana (UPI Kampus Cibiru, 2022)
The pandemic period provides several advantages for parents who have early childhood. The advantage is never replaced by money or material, that is togetherness with children. The togetherness has a good impact on children's emotional development. What is the role of parents during a pandemic to improve emotional early childhood? Researchers try to link the pandemic period with the activities parents carry out with their children at home. To find answers to questions, researchers used qualitative methods with literature studies. Researchers found that parents during the pandemic must be extra in educating, because parents must be friends, teachers and parents themselves. Furthermore, parents must train/teach knowledge in managing and expressing emotions completely both positive and negative emotions, being able to build relationships with other children and adults around them, and actively exploring the environment through learning. So, to get the ability of children who have good emotionality, the closeness of parents and children must be considered.